SOME ISSUES OF LEGAL PROVISION OF PUBLIC SAFETY - Ismailov, Isamidin; ogli, Narzullaev Otabek Saidulla (International Journal of Membrane Science and Technology, 2023)
This article analyzes the international normative legal documents and the national legislation of the Republic of Uzbekistan on ensuring public safety. Due to the fact that threats and aggressions to public security are increasing and their social danger is increasing, international documents on ensuring public security are being developed in the fields of combating terrorism and extremism, corruption, organized crime, illegal circulation of narcotics and psychotropic substances, human trafficking, as well as railway, air and automobile. classified into normative legal acts on ensuring safety in the fields of transport and traffic safety. In recent years, the reforms implemented in Uzbekistan to ensure public safety have been discussed, and some legal gaps in public safety, in particular, the need for legal protection of public safety during rallies, gatherings and demonstrations, have been justified. The importance of effective implementation of measures on public order and security is based on the activities of the Ministry of Internal Affairs and National Guard units, which are the main entities responsible for ensuring public safety during these events. It is also proposed to study social relations in the field of theoretical and legal provision of public safety based on their content, regulatory legal documents, and directions of activity of entities providing public safety.